Perkembangan Islam di Indonesia Era Reformasi - M Sauki (TASAMUH: Jurnal Studi Islam, 2018)
Islam in Indonesia has existed since in the 7th and became more widespread in the 13th. The success of Islam spread in Indonesia including the most dynamic with the method of cultural and political da'wah. Since the era of independence, Islam has grown rapidly. This paper aims to examine the existence of Islam in Indonesia today, with a review before the reform era and after reform. The Islamic movement can be said to be very influential on Indonesia's independence. This is evident from the role of Islamic organizations and parties. Despite its dominant influence, Islam did not become the official ideology of the Indonesian state after independence, as in the events of the Jakarta Charter, Islamic leaders preferred Pancasila as the principle of a pluralistic state. Uniquely, despite the predominantly Muslim population, Islam is not formally exposed in the system of government. After the Reform Era, many new Islamic parties and organizations were established. In Islamic conception, in general, reform is understood as ishlāh, which is in the ushul fiqh rules "keeping something good from the old and taking on the better of the new." Therefore, Islamic leaders are required to observe the global situation and its influence on Indonesia. Post reform also emerged a variety of radical Islamic organizations, terrorism, and movements that demand the implementation of Islamic law in all forms of order carried by certain Islamic movements, such as Hizbut Tahrir Indonesia and others. These problems make Islam a very sensitive issue: claims against Muslim representation, blasphemy, exclusivity and confusion between religion and politics without criticism. Such conditions precisely complicate the development of Islam in Indonesia that should consolidate and strengthen the interests of Islam. Furthermore, this condition is exacerbated also by the emergence of politicization and commercialization of Islamic identity in the context of da'wah, education and public media